2022
DOI: 10.1038/s41598-022-09117-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of needle-knife pre-cut papillotomy failure in patients with difficult biliary cannulation

Abstract: Predictors of needle-knife pre-cut papillotomy (NKP) failure for patients with difficult biliary cannulation has not been reported. Between 2004 and 2016, 390 patients with difficult biliary cannulation undergoing NKP were included in this single-center study. Following NKP, deep biliary cannulation failed in 95 patients (24.4%, NKP-failure group) and succeeded in 295 patients (75.6%, NKP-success group). Patient and technique factors were used to identify the predictors of initial NKP failure. Compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, needle-knife precut sphincterotomy (NKPS), which includes needle-knife papillotomy (NKP) and needle-knife stulotomy (NFK), does not consistently achieve SBC 10,11 . Our previous study indicated a signi cant association between PAD and NKP failure in univariate analysis, although not in multivariate analysis 12 . Given the variability of PAD among patients, the type of PAD may in uence the success of NKPS in PAD patients.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, needle-knife precut sphincterotomy (NKPS), which includes needle-knife papillotomy (NKP) and needle-knife stulotomy (NFK), does not consistently achieve SBC 10,11 . Our previous study indicated a signi cant association between PAD and NKP failure in univariate analysis, although not in multivariate analysis 12 . Given the variability of PAD among patients, the type of PAD may in uence the success of NKPS in PAD patients.…”
Section: Introductionmentioning
confidence: 84%
“…The details of ERCP and NKPS procedures were described in our previous study 12 . In short, the standard cannulation method using a cannula or sphincterotomy, and sometimes the double guidewire method by some endoscopists after the failure of the standard cannulation methods, were considered conventional cannulation methods in this study.…”
Section: Ercp and Nkps Proceduresmentioning
confidence: 99%
“…Difficult biliary cannulation was defined as more than five attempts at papillary cannulation, more than five minutes spent to cannulate after papilla was clearly visualized or more than one inadvertent PD cannulation. 9 Technical success was defined as free and deep instrumentation of the biliary tree. 8 Total time of the procedure was defined as the time from initial intubation to the procedure termination 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Difficult biliary cannulation was defined as more than five attempts at papillary cannulation, more than five minutes spent to cannulate after papilla was clearly visualized or more than one inadvertent PD cannulation. 8 …”
Section: Methodsmentioning
confidence: 99%
“…Difficult biliary cannulation was defined as more than five attempts at papillary cannulation, more than five minutes spent to cannulate after papilla was clearly visualized or more than one inadvertent PD cannulation. 8 Technical success was defined as free and deep instrumentation of the biliary tree. 7 Total time of the procedure was defined as the time from initial intubation to the procedure termination.…”
Section: Methodsmentioning
confidence: 99%